2014
DOI: 10.1021/cr4004874
|View full text |Cite
|
Sign up to set email alerts
|

Mn4Ca Cluster in Photosynthesis: Where and How Water is Oxidized to Dioxygen

Abstract: CONTENTS 1. Introduction 4175 2. Photosystem II 4176 2.1. Electron Transfer Chain 4176 2.2. Oxygen-Evolving Complex and the Mn 4 Ca Cluster 4177 2.3. X-ray Radiation Damage to the Metal Cluster 4179 3. Structural Changes of the Mn 4 CaO 5 Cluster during the Catalytic Cycle 4179 3.1. Dark Stable S 1 State Structure 4179 3.2. Structural Changes of the Mn 4 CaO 5 Cluster 4180 3.2.1. S 1 to S 2 (g = 2, MLS State) Transition 4181 3.2.2. S 1 to S 2 (g = 4 State) Transition 4181 3.2.3. S 2 to S 3 Transition 4181 3.2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

22
616
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 593 publications
(643 citation statements)
references
References 235 publications
(590 reference statements)
22
616
4
1
Order By: Relevance
“…oxygenases) and synthetic oxidation catalysts. [1][2][3][4][5] Many examples of natural and synthetic terminal high-valent Fe-oxygen, and Mn-oxygen species have been reported in the last decade. 6,7 In sharp contrast, and despite some efforts, detection of terminal high-valent metal-oxygen species involved in the mode of action of highly efficient oxidation catalysts based on late-transition metals such as cobalt, nickel or copper are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…oxygenases) and synthetic oxidation catalysts. [1][2][3][4][5] Many examples of natural and synthetic terminal high-valent Fe-oxygen, and Mn-oxygen species have been reported in the last decade. 6,7 In sharp contrast, and despite some efforts, detection of terminal high-valent metal-oxygen species involved in the mode of action of highly efficient oxidation catalysts based on late-transition metals such as cobalt, nickel or copper are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…
SummaryPhotosystem II (PSII) is a huge membrane-protein complex consisting of 20 different subunits with a total molecular mass of 350 kDa for a monomer, and catalyzes light-driven water oxidation at its catalytic center, the oxygen-evolving complex (OEC) [1][2][3] . The structure of PSII has been analyzed at 1.9 Å resolution by synchrotron radiation X-rays, which revealed that OEC is a Mn4CaO5 cluster organized in an asymmetric, "distorted-chair" form 4 .
…”
mentioning
confidence: 99%
“…This process also produces molecular oxygen as a byproduct; this "waste" oxygen is released to the atmosphere, where it plays an essential role in sustaining life on Earth. The catalytic site of water oxidation is a water-oxidizing center (WOC) located in the electron-donor side of PSII (1)(2)(3). Recent high-resolution (1.9-1.95 Å) X-ray crystallographic structures of PSII (4,5) revealed that the WOC core is an Mn 4 CaO 5 cluster fixed to the protein by six carboxylate [D1-D170, D1-E189, D1-E333, D1-D342, D1-A344 (C terminus), and CP43-E354] ligands and one imidazole (D1-H332) ligand.…”
mentioning
confidence: 99%